Duration of Playing Gadgets with Temper Tantrum of Emotional in Toddlers - Neng Kurniati; Novianti Novianti; Asmariyah Asmariyah (Jurnal EduHealth, 2023)
Temper tantrums are emotional disorders in children in the form of emotional outbursts characterized by crying, getting angry or slamming objects around them. Gadgets are a communication tool and can be used as a tool for children to play or watch. The purpose of this study was to determine the relationship between the duration of playing with gadgets and temper tantrums emotional in toddlers. The research was carried out in May 2022 in 30 sub-districts in Bengkulu City with a cross-sectional study approach. A sample of 166 toddlers was determined using a purposive sampling technique that has been known to play with gadgets. Data were analyzed using chi-square. The results obtained were 56 toddlers (33.7%) playing with gadgets ≤ 20 minutes per day and the remaining 110 toddlers (66.3%) playing with gadgets > 20 minutes every day. Toddlers with emotional temper tantrums were 108 (65.1%) and those who did not experience temper tantrums were 58 toddlers (34.9%). The duration of playing with gadgets has a significant relationship with temper tantrums of emotional in toddlers with p = 0.004. The OR value indicates the risk of temper tantrums of emotional in toddlers increasing 0.375 times who play with gadgets longer (> 20 minutes).